A comparative study of persulfate activation by iron-modified diatomite and traditional processes for the treatment of 17α-ethinylestradiol in water. Issue 21 (19th September 2021) - Silva-Rackov, Celyna K. O.; Silva, Silvia S. O.; Souza, Alessandra R.; Aguiar, Leandro G.; Silva, Dannielle J.; Vianna, Marilda M. G. R.; Nascimento, Claudio A. O.; Chiavone-Filho, Osvaldo
ABSTRACT: Emerging pollutants have been the subject of worldwide study because their continuous entry into the environment presents a risk to ecosystems and human health. Advanced oxidation processes show promise for eliminating or reducing the concentrations of emerging pollutants in water. This study aimed to investigate the treatment of aqueous systems containing the synthetic hormone 17α-ethinylestradiol. An innovative method for persulfate activation catalysed by iron-modified diatomite (heterogeneous system) was compared to conventional homogeneous activation methods (iron activation, alkaline activation, and heat activation). Iron-modified diatomite was more efficient in activating persulfate than traditional processes, achieving 98% of pollutant removal. Experimental results indicated that the catalyst can be reused without loss of removal efficiency, with potential environmental and economic benefits. GRAPHICAL ABSTRACT: UF0001